2006
DOI: 10.1192/apt.12.1.13
|View full text |Cite
|
Sign up to set email alerts
|

What works in alcohol use disorders?

Abstract: There has been much recent debate and criticism of UK alcohol policy (Drummond, 2004;Hall, 2005). Over the past 20 years, per capita alcohol consumption in Britain has increased by 31%, leading to large increases in the prevalence of alcoholic cirrhosis, alcohol-related violence and heavy alcohol use. Alcohol misuse causes at least 22 000 premature deaths each year and costs the taxpayer an estimated £20 billion (Prime Minister's Strategy Unit, 2003). The key features of alcohol dependence and harmful use are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Outside the educational context, Schwartz et al (2014) has shown that grocery shoppers can use precommitment contracts (i.e., promising to pay a higher bill if they do not meet a target goal) to help them make healthier food purchases. Likewise, some recovering alcoholics take drugs that create immediate symptoms of a severe hangover upon consumption of alcohol (Krampe et al, 2006;Luty, 2006).…”
Section: Situation Modificationmentioning
confidence: 99%
“…Outside the educational context, Schwartz et al (2014) has shown that grocery shoppers can use precommitment contracts (i.e., promising to pay a higher bill if they do not meet a target goal) to help them make healthier food purchases. Likewise, some recovering alcoholics take drugs that create immediate symptoms of a severe hangover upon consumption of alcohol (Krampe et al, 2006;Luty, 2006).…”
Section: Situation Modificationmentioning
confidence: 99%
“…Previous reviews of settings for treating alcohol misuse have concluded that there is no evidence for the superiority of in-patient over out-patient treatment (Miller 1986; Mattick 1993; Luty 2006). This has led to scrutiny of the more protracted admissions to residential rehabilitation.…”
Section: Residential Rehabilitationmentioning
confidence: 99%
“…This is the last of three articles updating my overview of what works for addiction published almost 10 years ago in this journal (Luty 2003, 2006). The first two articles considered new challenges for substance misuse services and recent developments in pharmacotherapy (Luty 2014, 2015).…”
mentioning
confidence: 96%
“…Two large studies have been conducted recently, in Europe, the United Kingdom Alcohol Treatment Trial (UKATT), and in U.S., the MATCH Project (Matching Alcoholism Treatments to Client Heterogeneity), the largest and most expensive study of its kind ever conducted (16) . They evaluated the results of different psychotherapeutic interventions.…”
Section: Effectiveness Of Psychotherapy and Combination Of Therapiesmentioning
confidence: 99%
“…The UKATT compared the motivational interviewing and SBNT (social behavior and network therapy), while the MATCH Project compared the motivational interviewing, CBT and facilitation approach of 12 steps. There were no statistical or clinically significant differences between the results of the evaluated treatments, as well as were found no evidence of the supposed beneficial effect of matching the type of therapy to the patient type (16)(17)(18) . Remained the argument that the results reinforced the idea that any kind of treatment would be better than none.…”
Section: Effectiveness Of Psychotherapy and Combination Of Therapiesmentioning
confidence: 99%